A combination of captopril challenge test after saline infusion test improves diagnostic accuracy for primary aldosteronism. (17th December 2019) - Lin, Chuan; Yang, Jun; Fuller, Peter J.; Jing, Huan; Song, Ying; He, Wenwen; Du, Zhipeng; Luo, Ting; Cheng, Qingfeng; Yang, Shumin; Wang, Hongman; Li, Qifu; et al.
Abstract: Context: The saline infusion test (SIT) is a common confirmatory test for primary aldosteronism (PA). According to the guideline, a postinfusion plasma aldosterone concentration (PAC) of 5‐10 ng/dL is considered indeterminate, and recommendations for diagnostic strategies are currently limited in this situation. Objective: To explore whether an addition of the captopril challenge test (CCT) could improve the diagnostic accuracy in patients with indeterminate SIT. Methods: A total of 280 hypertensive patients with high risk of PA completed this study. Subjects were defined as SIT indeterminate based on their PAC post‐SIT. These patients then underwent the CCT where PACs post‐CCT >11 ng/dL were considered positive. Using fludrocortisone suppression test (FST) as the reference standard, diagnostic parameters including area under the receiver‐operator characteristic curves (AUC), sensitivity and specificity were calculated. Results: There were 65 subjects (23.2%) diagnosed as PA indeterminate after SIT. With the addition of CCT, true‐positive numbers increased from 134 to 147, and false‐negative numbers decreased from 27 to 14. Compared to SIT alone, a combination of SIT and CCT showed a higher AUC (0.91 [0.87, 0.94] vs 0.87 [0.83, 0.91], P = .041) and an increased sensitivity for the diagnosis of PA (0.91 [0.86, 0.95] vs 0.83 [0.76, 0.89], P = .028), while the specificity remained similar. In the subgroup with indeterminate SIT results, using PAC post‐CCT resulted in a 36% higher AUC than using PAC post‐SIT alone for the diagnosis of PA. Conclusion: For patients under investigation for possible PA who have indeterminate SIT results, an addition of CCT improves the diagnostic accuracy.